FACTORS AFFECTING THE CHOICE OF AMALGAM OR COMPOSITE FOR POSTERIOR DENTAL RESTORATIONS IN STUDENTS OF ISLAMIC INTERNATIONAL DENTAL COLLEGE (IIDC) - TAJ , R; SHARAFAT , M; NAWAZ , H; ZAHRA , S; RUBAB , S; HASAN , U (Biological and Clinical Sciences Research Journal, 2024)
Restorative materials such as composite and amalgam are widely used in dental practice. Various factors, including ease of use, handling, and patient preference, influence dental students' preferences for these materials. Understanding these factors is important for curriculum development and clinical practice in dental education. Objective: This study aimed to evaluate the preference of dental students at Islamabad Institute of Dental Sciences (IIDC) between composite and amalgam for restorative procedures and to identify the factors influencing this choice. Methods: A questionnaire-based cross-sectional study was conducted at IIDC Hospital. A total of 76 questionnaires were distributed to 3rd and final-year dental students. The data were collected and statistically analyzed using SPSS version 23. Descriptive statistics were used to summarize the data, and factors influencing material choice were analyzed. Results: Of the students surveyed, 90.8% preferred composite for its easier cavity preparation, while 9.2% favored amalgam. 61.8% of students considered composite easier to handle, whereas 38.2% believed amalgam was easier. 81.6% of students selected composite as their material of choice, and 53.9% considered composite a better substitute for amalgam. Meanwhile, 46.1% thought amalgam was a superior alternative to composite. Regarding patient preference, 84.2% of students reported that patients preferred composite, while 14.5% believed patients favored amalgam. Conclusion: This study's results indicate that most dental students at IIDC prefer composite over amalgam for posterior restorations. This preference is likely influenced by the ease of use, handling properties, and patient preference for composite. The clinical training environment of the dental institute may also play a role in shaping these preferences.